Diversity of Trends of Viremia and T-Cell Markers in Experimental Acute Feline Immunodeficiency Virus Infection - Roche, Sylvain (Public Library of Science, 2013)
OBJECTIVE: The early events of human immunodeficiency virus infection seem critical for progression toward disease and antiretroviral therapy initiation. We wanted to clarify some still unknown prognostic relationships between inoculum size and changes in various immunological and virological markers. Feline immunodeficiency virus infection could be a helpful model. METHODS: Viremia and T-cell markers (number of CD4, CD8, CD8β(low)CD62L(neg) T-cells, CD4/CD8 ratio, and percentage of CD8β(low)CD62L(neg) cells among CD8 T-cells) were measured over 12 weeks in 102 cats infected with different feline immunodeficiency virus strains and doses. Viremia and T-cell markers trajectory groups were determined and the dose-response relationships between inoculum titres and trajectory groups investigated. RESULTS: Cats given the same inoculum showed different patterns of changes in viremia and T-cell markers. A statistically significant positive dose-response relationship was observed between inoculum titre and i) viremia trajectory-groups (r = 0.80, p<0.01), ii) CD8β(low)CD62L(neg) cell-fraction trajectory-groups (r = 0.56, p<0.01). Significant correlations were also found between viremia and the CD4/CD8 ratio and between seven out of ten T-cell markers. CONCLUSIONS: In cats, the infectious dose determines early kinetics of viremia and initial CD8+ T-cell activation. An expansion of the CD8β(low)CD62L(neg) T-cells might be an early predictor of progression toward disease. The same might be expected in humans but needs confirmation.